Digital Transformation of Human Resource Management and Its Implications for Employee Productivity and Accounting Information Systems: Evidence from Azerbaijan - Masim Vagif Nadirli (Journal of Business Innovation and Accounting Research, 2026)
Digital transformation is reshaping human resource management (HRM) by automating administrative processes, expanding data-driven decision-making, and changing how employees access organizational services. Yet evidence remains limited on whether digital HRM is simultaneously associated with employee productivity and the quality of accounting information systems (AIS), particularly in transitional economies. This study examines these relationships using a cross-sectional survey of 250 employees working in public- and private-sector organizations in Azerbaijan. The reported analyses combine descriptive statistics, multiple regression, one-way analysis of variance, Pearson correlations, and mediation analysis. Digital HR processes were the strongest reported predictor of HRM effectiveness (β = .385, p < .001), followed by digital infrastructure (β = .298), employee digital skills (β = .248), and top-management support (β = .178). Organizations categorized as highly digitalized reported higher task completion, work quality, innovation, decision speed, and collaboration than organizations with lower digitalization levels. Digital transformation was also positively correlated with AIS quality (r = .652, p < .01) and organizational performance (r = .718, p < .01). The reported mediation results suggest that HRM/HRD mechanisms partially transmit the association between digital transformation and employee productivity, whereas AIS quality partially transmits the association between digital transformation and organizational performance. The study contributes an integrative perspective linking digital HRM and AIS in Azerbaijan. Because the design is cross-sectional and based on self-reported data, the findings should be interpreted as associations rather than causal effects.